2020
DOI: 10.3390/f11030318
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Photosynthetic Capacity of Sunlit and Shaded Mature Leaves in a Deciduous Forest

Abstract: A clear understanding of the dynamics of photosynthetic capacity is crucial for accurate modeling of ecosystem carbon uptake. However, such dynamical information is hardly available and has dramatically impeded our understanding of carbon cycles. Although tremendous efforts have been made in coupling the dynamic information of photosynthetic capacity into models, using “proxies” rooted from the close relationships between photosynthetic capacity and other available leaf parameters remains the popular selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 81 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…SLA correlates highly with mass-based photosynthesis and respiration rates (Wright et al 2004). However, Song et al (2020) found a signi cant correlation between LMA and maximum carboxylation rate (V max ) for leaves grown under shade. In addition, leaves with higher LMA are physically more robust and less prone to herbivory (Sterck et al 2006).…”
Section: Discussionmentioning
confidence: 95%
“…SLA correlates highly with mass-based photosynthesis and respiration rates (Wright et al 2004). However, Song et al (2020) found a signi cant correlation between LMA and maximum carboxylation rate (V max ) for leaves grown under shade. In addition, leaves with higher LMA are physically more robust and less prone to herbivory (Sterck et al 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the Cj model calculated canopy resistance by combining the sunlit and shaded leaves to calculate canopy transpiration (Ding et al, 2014; Zhang, Liu, et al, 2011). The sunlit and shaded leaves have obviously different radiation environments, indicating that the two kinds of leaves have an intrinsic difference in physiological activities (Song et al, 2020). The sunlit and shaded leaves LAI drove the stomatal resistance to different radiation environments (Irmak et al, 2008), which improved the accuracy of the canopy transpiration in the Cj model.…”
Section: Discussionmentioning
confidence: 99%
“…The plots were sampled in spring, summer, autumn, and winter. Representative trees were identified, and fresh leaves were collected from the first live branches in the east, south, west, north, and center directions [ 21 ]. Three 5 × 5 m plots were set up to collect litter, humus, and soil.…”
Section: Methodsmentioning
confidence: 99%